Tolerability and Efficacy of Rivaroxaban vs Warfarin for Non Valvular Atrial Fibrillation - Mahboob Ur Rehman, Asma Rauf, Amjad Ali Shah, Anwar Ali, Amjad Abrar, Malik Ali Raza (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and is seen in 1–2% of the general population. Objectives: The main objective of the study is to find the tolerability and efficacy of rivaroxaban Vs warfarin for non valvular atrial fibrillation. Material and methods: This cross sectional comparative study was conducted in Pakistan Institute of Medical Sciences Islamabad during January 2021 to June 2021. After permission from hospital ethical committee, total 70 patients meeting the inclusion and exclusion criteria was enrolled in the study from OPDs of cardiology and allied Departments of hospital. Detailed history and physical examination was done to meet the inclusion and exclusion criteria. Informed consent was obtained. Results: Out of 70 patients enrolled in total, 15 were excluded because of the above-mentioned exclusion criteria; 6 patients of NOAC group denied to participate and left cohort; and 4 patients lost the follow-up. Out of 45 participants, 21 were treated with rivaroxaban, while 24 were treated with warfarin. Conclusion: It is concluded that oral anticoagulant drugs for prevention of stroke in non-valvular AF have been evolved and adding new options and advantages for patients and physicians such as fewer frequency of drug and food interactions, no need for monitoring, broad therapeutic index and tolerated better by patients.